UJI EFEKTIVITAS ASAP CAIR CANGKANG BUAH Hevea braziliensis TERHADAP AKTIVITAS BAKTERI Escherichia coli - Dinda Oktarina; Sumpono Sumpono; Rina Elvia (ALOTROP, 2017)
This research purpose to determine the effectiveness of the liquid smoke of the Hevea braziliensis  fruit shell  against the activity of Escherichia coli bacteria. The preparation and purification of liquid smoke is carried out by 4 stages: pyrolysis , sedimentation, stage 1 and stage  2  distillation. This research was started with total acidity test, phenol level, pH and density with result of measurement 4,725% total acid content, 0,84% phenol content, 2,548 pH and 1,004 in density . An antibacterial test  using disc diffusion method by looking at the diameter of the clear zone. There are six concentrations of liquid smoke of  H.braziliensis  rubber shell used, negative control using aquades and positive control using ciprofloxacin . An  effective concentration was found in inhibiting E.coli is 100% concentration with a clear zone diameter of 11.3 mm. The result of analysis using One Way ANOVA showed F count (4.42)> F table (3,23), then H0 rejected, meaning there is a significant difference of influence of concentration to the diameter of clear zone produced.